Vulnerabilità e agentività nella sfera più intima. Una ricerca su operatori socio-sanitari, familiari e badanti nell’assistenza domiciliare alla persona disabile anziana - Massimiliano Minelli; Veronica Redini (AM. Rivista della Società Italiana di Antropologia Medica, 2012)
Vulnerability and agency in the intimate sphere. An investigation of health workers, family members, and migrant care-givers engaged in home care assistance for elders with disabilities Forms of assistance – in-home caregiving, domestic and organisational assistance – aimed at elders with disabilities are in this article addressed through a definition of space in a micro-political perspective. This space, which tends to be standardized according to contemporary biomedical, bureaucratic and economic-administrative parameters, is observed ethnographically by focusing on agency developed in the interaction between employees in the field of assistance – health and social workers, family members and migrant caregivers – and the users of these services. This article analyses everyday experiences in the intimate sphere of the home of the patient and the chains of interaction that unfold in the public sphere. Based on this analysis, we propose to rethink the vulnerability experienced by all involved subjects in relation to the recognition of rights and political participation. Furthermore, the reconstruction of specific relations of dependency and intimacy allows us to highlight the ways in which the various subjects are invested with professional status and act continuously on the boundaries between formal and informal spheres. To this end, we show how the presence of female migrants engaged in domestic work plays a strategic role in shaping a critical perspective on the links between power relations, agency and vulnerability in relation to care.Keywords: relationships of care; disabilities; agency; vulnerability; health policies; relations of force; elders caregiving; female migrants. Vulnerabilità e agentività nella sfera più intima. Una ricerca su operatori socio-sanitari, familiari e badanti nell’assistenza domiciliare alla persona disabile anziana Le forme di assistenza – domestica, domiciliare, tutelare – rivolte alla popolazione anziana sono affrontate attraverso una definizione in chiave politica dello spazio di cura. Tale spazio, che tende a essere oggi standardizzato secondo parametri biomedici, burocratici ed economico-amministrativi, è osservato etnograficamente mettendo al centro l’agentività sviluppata nella interazione fra datori di cura – operatori sociosanitari, familiari e badanti – e utenti. L’analisi dell’esperienza quotidiana nella sfera intima della dimora del paziente e delle catene di azioni che si allargano nella sfera pubblica è alla base di una rilettura della vulnerabilità di tutti i soggetti attivi nello scambio sociale, in rapporto alla questione del riconoscimento dei diritti e della partecipazione politica. La ricostruzione di specifici rapporti di dipendenza e di intimità permette inoltre di evidenziare i modi in cui i diversi soggetti coinvolti nelle interazioni sono investiti di uno status professionale e agiscono continuamente sul confine tra sfere formali e informali. A tal fine, la presenza di donne straniere impegnate nel lavoro domestico assume un ruolo strategico nel delineare una prospettiva critica sui legami tra rapporti di forza, agentività e vulnerabilità nella relazione di cura.Parole chiave: relazione di cura; disabilità; agentività; vulnerabilità; politiche di salute; rapporti di forza; assistenza alla condizione anziana; donne migranti.